Exploring EFL Students’ Perceptions of QuillBot as an AI-Powered Paraphrasing Tool in Thesis Writing - Friska Indria; Amalia Hasanah; Winny Agustia Riznanda (Universitas Nusantara PGRI Kediri, 2026)
Paraphrasing skills hold significant value in academic writing, specifically in undergraduate thesis and proposal writing, to avoid plagiarism. QuillBot, an AI-powered paraphrasing tool, aided students in producing better writing. This research explored how students perceived the use of QuillBot in supporting their academic writing, mainly in writing a proposal and thesis. The study used a qualitative approach with a case study design. Seven students from the eighth semester of the English Education Study Program at UIN Raden Fatah Palembang were selected as participants. The selection of participants in this study was conducted by purposive homogeneous sampling. Data were gathered through semi-structured interviews and thematic analysis was employed to analyze the findings. The results of the study showed that students considered QuillBot to have advantages in discovering synonyms quickly, enhancing clarity and meaning in writing, enhancing vocabulary acquisition, saving time, being easy to utilize, and connecting with various platforms. However, students also recognized the weaknesses of using QuillBot, such as the need to double-check the results and the risk of over-reliance on technology. In conclusion, QuillBot was perceived as an effective tool if used in balance with independent writing practice to enhance writing skills. This study implies that AI-based paraphrasing tools are a supportive resource for academic writing, provided that students are taught to use them critically and avoid overreliance on such tools.